2014
DOI: 10.1164/rccm.201306-1061oc
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Study of Percent Emphysema on Computed Tomography in the General Population. The Multi-Ethnic Study of Atherosclerosis Lung/SNP Health Association Resource Study

Abstract: Our results suggest that some genes previously identified as influencing lung function are independently associated with emphysema rather than lung function, and that genes related to α-mannosidase may influence risk of emphysema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
77
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 47 publications
1
77
0
Order By: Relevance
“…In a normal population including never-smokers, differences in percent emphysema may occur because of altered stretch or compression of the lung related to gravity, height of the lung and support of the heart (1,25), variation in residual peripheral airway structures (a voxel inside an airway will be emphysema-like), and scatter effects (26), which differ by scanner manufacturer, or may represent the presence of subclinical emphysema due to secondhand smoke exposure during childhood and other environmental exposures, as well as genetic factors (27)(28)(29)(30)(31)(32). Indeed, researchers in small studies have suggested that percent emphysema varies among healthy never-smokers by demographic factors (33)(34)(35)(36); however, these studies were limited by modest sample sizes, restricted racial and ethnic distributions, and lack of population-based sampling.…”
mentioning
confidence: 99%
“…In a normal population including never-smokers, differences in percent emphysema may occur because of altered stretch or compression of the lung related to gravity, height of the lung and support of the heart (1,25), variation in residual peripheral airway structures (a voxel inside an airway will be emphysema-like), and scatter effects (26), which differ by scanner manufacturer, or may represent the presence of subclinical emphysema due to secondhand smoke exposure during childhood and other environmental exposures, as well as genetic factors (27)(28)(29)(30)(31)(32). Indeed, researchers in small studies have suggested that percent emphysema varies among healthy never-smokers by demographic factors (33)(34)(35)(36); however, these studies were limited by modest sample sizes, restricted racial and ethnic distributions, and lack of population-based sampling.…”
mentioning
confidence: 99%
“…We are aware of only two genome-wide association studies (GWAS) of lung function or COPD-related phenotypes that analyzed Hispanics separately (13,15). One identified a novel variant near MAN2B1 that was associated with percent emphysema on computed tomography (CT) (16) and the other identified two loci that approached genome wide statistical 4 significance for COPD (13).…”
Section: Examination Of Genetic Risk Among Non-european Populations Mmentioning
confidence: 99%
“…We are aware of only two genome-wide association studies (GWAS) of lung function or COPD-related phenotypes that analyzed Hispanics separately (13,15). One identified a novel variant near MAN2B1 that was associated with percent emphysema on computed tomography (CT) (16) and the other identified two loci that approached genome wide statistical 4 significance for COPD (13). This literature contrasts with that among persons of European ancestry, in whom GWAS have identified multiple loci in genes for lung function and COPD (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) To improve our current understanding of the genetic architecture of lung functionrelated traits in Hispanics/Latinos, we performed a meta-analysis for FEV1, FEV1/FVC, airflow limitation and COPD among six Hispanic/Latino groups in the HCHS/SOL cohort (10,32).…”
Section: Examination Of Genetic Risk Among Non-european Populations Mmentioning
confidence: 99%
“…Also in 2014, Manichaikul et al identified associations in percentage emphysema using computed tomography scans (Table 6). Furthermore, on comparison of upper and lower lobes in the CT scans of Hispanic individuals, a difference in emphysema lobe ratio was found to be associated with a SNP in MAN2B1 (Manichaikul et al, 2014). A separate study by Castaldi et al used the quantification results of computed tomography emphysema to identify SNPs associated with 4 distinct patterns of emphysema (normal, moderate centrilobular, severe centrilobular and panlobular) .…”
Section: Refining Copd Snp Associationsmentioning
confidence: 99%